Penjualan Konten Sensual Melalui Akun Alter Ego di Media Sosial X Ditinjau dari Teori Space Transition - Rizki Kurnia Putra; Triny Srihadiati (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the sale of sensual content through alter ego accounts on X social media, examined through the lens of the Space Transition theory, with a focus on how the virtual world allows individuals to explore alternative identities and freedom of expression. Based on interviews with three informants, the results indicate that their primary motivation for using alter ego accounts is to maintain privacy and explore aspects of themselves that cannot be displayed in the real world. This study then evaluates the findings using the Space Transition theory, which posits that the virtual world provides a space for individuals to transcend the limitations of the real world, enabling them to construct new identities free from the social norms that prevail in reality. The study concludes that while the virtual world offers freedom and opportunities to explore other aspects of individuals' nature and behavior in the real world, with the goal of being freed from social norms, individuals may still face long-term consequences from their activities in the virtual world, particularly in the case of selling sensual content